Extranodal NK/T-cell lymphoma, nasal type–a case report and a review of the literature - Zhan, Yu; Sun, Na (Frontiers in Oncology, 2025)
Nasal-type extranodal NK/T-cell lymphoma (ENKTCL) is a unique type of mature NK/T-cell lymphoma that is closely related to the EBV virus (EBV). In most cases, ENKTCL occurs in the nasal cavity and other parts of the upper respiratory and digestive tract, and its clinical presentation is usually unremarkable, making it difficult to early diagnosis. We report a case of NK/T-cell lymphoma and its main clinical features and cytopathological characteristics.